THE EFFECT OF WORK MOTIVATION ON EMPLOYEE PERFORMANCE OF REGIONAL DRINKING WATER COMPANY (PDAM) IN TELLU LIMPOE DISTRICT IN SIDENRENG RAPPANG REGENCY - Nur Fajriani; Fadlina; Ari Ayu (Jurnal Mahasiswa Manajemen, 2025)
The aim of this research is to determine the effect of work motivation on the performance of employees of the Regional Drinking Water Company (PDAM) of Sidenreng Rappang Regency. This research method uses quantitative methods with a descriptive approach. This type of research is a survey to obtain information in the field. The data used is primary data obtained from the field using a questionnaire as a data collection tool. Questionnaires were distributed to 30 PDAM employees. Then, the data was processed using the SPSS program. The data analysis method uses simple regression analysis. The results of the analysis show that work motivation has a positive and significant effect on the performance of employees of the Regional Drinking Water Company (PDAM) of Sidenreng Rappang district.